JMJD5 regulates PKM2 nuclear translocation and reprograms HIF-1α–mediated glucose metabolism - Wang, Hung-Jung; Hsieh, Ya-Ju; Cheng, Wen-Chi; Lin, Chun-Pu; Lin, Yu-shan; Yang, So-Fang; Chen, Chung-Ching; Izumiya, Yoshihiro; Yu, Jau-Song; Kung, Hsing-Jien; Wang, Wen-Ching (Proceedings of the National Academy of Sciences - PNAS, 2014)
JMJD5, a Jumonji C domain-containing dioxygenase, is important for embryonic development and cancer growth. Here, we show that JMJD5 is up-regulated by hypoxia and is crucial for hypoxia-induced cell proliferation. JMJD5 interacts directly with pyruvate kinase muscle isozyme (PKM)2 to modulate metabolic flux in cancer cells. The JMJD5-PKM2 interaction resides at the intersubunit interface region of PKM2, which hinders PKM2 tetramerization and blocks pyruvate kinase activity. This interaction also influences translocation of PKM2 into the nucleus and promotes hypoxia-inducible factor (HIF)-1α–mediated transactivation. JMJD5 knockdown inhibits the transcription of the PKM2–HIF-1α target genes involved in glucose metabolism, resulting in a reduction of glucose uptake and lactate secretion in cancer cells. JMJD5, along with PKM2 and HIF-1α, is recruited to the hypoxia response element site in the lactate dehydrogenase A and PKM2 loci and mediates the recruitment of the latter two proteins. Our data uncover a mechanism whereby PKM2 can be regulated by factor-binding–induced homo/heterooligomeric restructuring, paving the way to cell metabolic reprogram.